SAT0238 Rapid elevation of erythrocyte methotrexate-polyglutamate3 (MTX-PG3) levels related to the efficacy of mtx in patients with rheumatoid arthritis (RA). (12th June 2018) - Nishida, M.; Tsuji, G.; Takahashi, M.; Saitou, T.; Noda, Y.; Yoneda, K.; Amano, N.; Sendo, S.; Onishi, A.; Morinobu, A.; Shinohara, M.; Kumagai, S.
Abstract : Background: MTX is transported into cells and retained long after polyglutamation. Recently, it has been described that the response to MTX treatment is related to the intracellular MTX-polyglutamate (MTX-PG) levels, but little is known about its details and determinants 1) . Objectives: To clarify the association of erythrocyte concentrations of MTX-PGs (PG1 to PG4) with the efficacy of MTX in 35 MTX naïve patients with RA. Methods: We measured erythrocyte MTX-PGs at 4, 12, 24, and 48 weeks after administration of MTX using liquid chromatography (LC)-mass spectrometry (MS)/MS assay. The associations of MTX-PG concentrations with disease activity and the 9 SNPs including 5 SNPs reported for associations with MTX-efficacy were analyzed. Results: As shown in the figure, MTX-PG1 and PG2 elevated at week 4, and total MTX-PGs as well as MTX-PG3 and MTX-PG4 increased until week 12. The MTX-PG2 fraction (as percentage of total) was 26% to 29% and almost constant throughout the course. MTX-PG3 and MTX-PG4 fractions were gradually elevated over time, although MTX-PG1 fraction was decreased. A negative association of Disease Activity Score in 28 joints (DAS28) at week 4, 12 and 24 was observed with levels of MTX-PG2 (p=0.008), MTX-PG3 (p=0.0045), MTX-PG4 (p=0.0142) and total MTX-PG (p=0.023). On the other hand, ΔDAS28 (change in DAS28 scores from baseline) was positively correlated to fraction of MTX-PG3 (p=0.011) but negatively correlated to that of MTX-PG1 (p=0.0071). At week 12 and 24, MTX-PG2 fraction was higher (p=0.0783) in the patients who achieved the EULAR good response criteria than in those who did not. MTX-PG3 levels were associated with SLC19A1c.80G>A and FMO2_c.585A>G, and the fraction of MTX-PG2 in total MTX-PGs was associated with GGH c.452C>T and with FMO2_c.585A>G. Conclusions: This study suggests that rapid elevation of erythrocyte MTX-PG3 levels from MTX-PG1 through MTX-PG2 and higher distribution of MTX-PG3 is important to exert certain efficacy of MTX. We previously reported in retrospective study that MTX-PG concentration in RA patients keeping remission for long time was associated with several SNPs 2 ), and some of the results were confirmed in this prospective study. References: 1) de Rotte MCFJ, et al. Ann Rheum Dis, 2015;74:408–414. 2) Kumagai S, et al. Ann Rheum Dis76(Suppl2)282. doi:10.1136/annrheumdis-2017-eular.2585 Disclosure of Interest: None declared